Implementasi Kebijakan Interactive Flat Panel dan Implikasinya Terhadap Pembelajaran Berbasis Kebutuhan Masyarakat di Kabupaten Bojonegoro: Perspektif Filsafat Pendidikan Indonesia - Ansachul Balaya; A. Rofiq Ghozali; Siti Arofah; Gunarti Dwi Lestari; Ima Widiyanah (Continuous Education: Journal of Science and Research, 2026)
Digital technology has evolved beyond a learning aid into a medium for creating more interactive and meaningful learning experiences. This study aims to analyze the implementation of the IFP distribution policy and its implications for community needs-based learning from the perspective of Indonesian educational philosophy in Bojonegoro Regency. This study employed a qualitative approach using a case study design. The research was conducted at SMAN 1 Bojonegoro, SMPN 1 Trucuk Bojonegoro, and SMPN 1 Kedewan Bojonegoro. Participants consisted of principals, teachers, vice principals for curriculum or facilities, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive qualitative techniques involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the IFP distribution policy has generally succeeded in supporting the digital transformation of the education system. The use of IFP enhances classroom interactivity, learning motivation, and student engagement through touchscreen features, visual media, learning videos, and educational games. However, challenges remain, including limited device availability, inadequate teacher training, and the absence of systematic monitoring and evaluation. From the perspective of Indonesian educational philosophy, the policy reflects educational adaptation to technological advancement while remaining aligned with the values of progressivism and Ki Hadjar Dewantara’s philosophy. Nevertheless, IFP utilization is still concentrated on modernizing instructional media rather than addressing local community needs. Strengthening teacher capacity, contextual learning practices, and the digital learning ecosystem is therefore essential to maximize the policy’s effectiveness and sustainability.